Origins of green turtle fishery bycatch in the central Pacific revealed by mixed genetic markers - Horne, John B.; Roden, Suzanne E.; LaCasella, Erin L.; Frey, Amy; Martin, Summer L.; Jones, T. Todd; Murakawa, Shawn; Brunson, Shandell; Balazs, George H.; Dutton, Peter H. (Frontiers in Marine Science, 2023)
Longline fishing vessels, such as those that target tuna or billfish, also unintentionally catch endangered marine turtle species on the high seas. The stock composition of this bycatch is often unknown but potentially complex, with individuals coming from many possible origins on an ocean-basin scale. To better understand the stock composition of green turtle (Chelonia mydas) bycatch we obtained 46 turtles, 27-91 cm in curved carapace length, caught by Hawaii- and American Samoa-based pelagic longline fishing vessels across large areas of the North- and South-central Pacific. We genotyped these at nine microsatellite loci and one mitochondrial DNA marker, and used a baseline of 1,043 nesting female green turtles from beaches across the Pacific for population assignment and mixed-stock analysis. By analyzing both marker types jointly we were able to increase power and genetically resolve ten baseline stocks of nesting females with mean self-assignment and simulated accuracies of 75-97%. Above the Equator, green turtle bycatch was composed mostly of individuals from Hawaiian and Eastern Pacific stocks, with a small number from the Western Pacific. Below the Equator, the most common stocks in the bycatch were from Australia and the Coral Sea, American Samoa and French Polynesia, and the Galápagos Islands. Overall, turtles originating from East, West, and Central Pacific breeding populations were major components of the bycatch, suggesting that the geographic ranges of these populations overlap across large tracts of ocean during the pelagic life history stages.